Pressure UlceR Programme Of reSEarch (PURPOSE): using mixed methods (systematic reviews, prospective cohort, case study, consensus and psychometrics) to identify patient and organisational risk, develop a risk assessment tool and patient-reported outcome Quality of Life and Health Utility measures - Jane Nixon; E Andrea Nelson; Claudia Rutherford; Susanne Coleman; Delia Muir; Justin Keen; Christopher McCabe; Carol Dealey; Michelle Briggs; Sarah Brown; Michelle Collinson; Claire T Hulme; et al. (NIHR Journals Library, 2015)
Background: The Pressure UlceR Programme Of reSEarch (PURPOSE) consisted of two themes. Theme 1 focused on improving our understanding of individuals' and organisational risk factors and on improving the quality of risk assessments (work packages 1-3) and theme 2 focused on developing patient-reported outcome measures (work packages 4 and 5). Methods: The programme comprised 21 individual pieces of work. Pain: (1) multicentre pain prevalence study in acute hospitals, (2) multicentre pain prevalence study in community localities incorporating (3) a comparison of case-finding methods, and (4) multicentre, prospective cohort study. Severe pressure ulcers: (5) retrospective case study, (6) patient involvement workshop with the Pressure Ulcer Research Service User Network for the UK (PURSUN UK) and (7) development of root cause analysis methodology. Risk assessment: (8) systematic review, (9) consensus study, (10) conceptual framework development and theoretical causal pathway, (11) design and pretesting of draft Risk Assessment Framework and (12) field test to assess reliability, validity, data completeness and clinical usability. Quality of life: (13) conceptual framework development (systematic review, patient interviews), (14 and 15) provisional instrument development, with items generated from patient interviews [from (1) above] two systematic reviews and experts, (16) pretesting of the provisional Pressure Ulcer Quality of Life (PU-QOL) instrument using mixed methods, (17) field test 1 including (18) optimal mode of administration substudy and item reduction with testing of scale formation, acceptability, scaling assumptions, reliability and validity, and (19) field test 2 - final psychometric evaluation to test scale targeting, item response categories, item fit, response bias, acceptability, scaling assumptions, reliability and validity. Cost-utility: (20) time trade-off task valuations of health states derived from selected PU-QOL items, and (21) validation of the items selected and psychometric properties of the new Pressure Ulcer Quality of Life Utility Index (PUQOL-UI). Key findings: Pain: prevalence studies - hospital and community patients experience both pressure area-related and pressure ulcer pain; pain cohort study - indicates that pain is independently predictive of category 2 (and above) pressure ulcer development. Severe pressure ulcers: these were more likely to develop in contexts in which clinicians failed to listen to patients/carers or recognise/respond to high risk or the presence of an existing pressure ulcer and services were not effectively co-ordinated; service users found the interactive workshop format valuable; including novel components (interviews with patients and carers) in root cause analysis improves the quality of the insights captured. Risk assessment: we developed a Pressure Ulcer Risk Assessment Framework, the PURPOSE-T, incorporating the Minimum Data Set, a screening stage, a full assessment stage, use of colour to support decision-making, and decision pathways that make a clear distinction between patients with an existing pressure ulcer(s) (or scarring from previous ulcers) who require secondary prevention and treatment and those at risk who require primary prevention (http://medhealth.leeds.ac.uk/accesspurposet). Quality of life: the final PU-QOL instrument consists of 10 scales to measure pain, exudate, odour, sleep, vitality, mobility/movement, daily activities, emotional well-being, self-consciousness and appearance, and participation (http://medhealth.leeds.ac.uk/puqol-ques). Cost-utility: seven items were selected from the PU-QOL instrument for inclusion in the PUQOL-UI (http://medhealth.leeds.ac.uk/puqol-ui); secondary study analysis indicated that item selection for the PUQOL-UI was appropriate and that the index was acceptable to patients and had adequate levels of validity. Conclusions: The PURPOSE programme has provided important insights for pressure ulcer prevention and treatment and involvement of service users in research and development, with implications for patient and public involvement, clinical practice, quality/safety/health service management and research including replication of the pain risk factor study, work exploring 'best practice' settings, the impact of including skin status as an indicator for escalation of preventative interventions, further psychometric evaluation of PU-QOL and PUQOL-UI the measurement of 'disease attribution.' Funding: The National Institute for Health Research Programme Grants for Applied Research programme.